2020
DOI: 10.3390/toxins12020138
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Ozone and Electron Beam Irradiation on Degradation of Zearalenone and Ochratoxin A

Abstract: Zearalenone (ZEN) and ochratoxin A (OTA) are key concerns of the food industry because of their toxicity and pollution scope. This study investigated the effects of ozone and electron beam irradiation (EBI) on the degradation of ZEN and OTA. Results demonstrated that 2 mL of 50 μg/mL ZEN was completely degraded after 10 s of treatment by 2.0 mg/L ozone. The degradation rate of 1 μg/mL ZEN by 16 kGy EBI was 92.76%. Methanol was superior to acetonitrile in terms of degrading ZEN when the irradiation dose was hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(19 citation statements)
references
References 24 publications
0
18
0
1
Order By: Relevance
“…Physical methods mainly include ultraviolet radiation, heat treatment, and X-ray treatment [11], but these physical techniques have not been widely used because of their low degradation rate and possible damage to food. Commonly used chemical methods include ozone treatment [12], reducing agents, and alkali treatment. However, chemical methods are difficult for food safety organizations to adopt because chemical degradation agents are retained in food, and mycotoxins have low degradation efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…Physical methods mainly include ultraviolet radiation, heat treatment, and X-ray treatment [11], but these physical techniques have not been widely used because of their low degradation rate and possible damage to food. Commonly used chemical methods include ozone treatment [12], reducing agents, and alkali treatment. However, chemical methods are difficult for food safety organizations to adopt because chemical degradation agents are retained in food, and mycotoxins have low degradation efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…Chemical methods are based on the application of chemicals such as ammonia, hydrogen peroxide, sodium hypochlorite and ozone [1]. Since ozone is safe, efficient and environmental friendly, it is widely used for detoxification of the toxin [227]. A study by Qi, et al [228] indicated that ozone has the potential to significantly reduce ZEN in naturally contaminated corn without affecting its quality.…”
Section: Degradation Kineticsmentioning
confidence: 99%
“…Some solvents have a radical scavenging effect, thus reducing the effect of EB radiation. For example, it was shown that the EB dose increase from 0 to 6 kGy gives different results in methanol and in acetonitrile solution both containing zearalenone and ochratoxin A [ 93 ]. The rate of mycotoxin degradation was significantly lower in the methanol solution.…”
Section: Electron Beam (Eb) Radiationmentioning
confidence: 99%
“…However, EB remains a promising technology to degrade mycotoxins, although it may also have adverse effects on the quality of edible materials, especially by increasing the irradiation dose. In this concern, a decrease in amylose content, essential and total amino acid contents, and starch crystallinity has been observed in treated corns by the EB dose increase from 10 to 30 kGy [ 93 ]. Electrons produced by EB may penetrate to deeper sections of matrix, which can result in changes in the color quality via the splitting of carotenoids and oxidation of lipids, the rancidity via producing free fatty acids, variation in the viscosity via degradation of starch, and some alteration in sensory properties of foods [ 86 , 91 ].…”
Section: Electron Beam (Eb) Radiationmentioning
confidence: 99%